2021
DOI: 10.1017/s0022029921000406
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Comprehensive Climate Index to estimate heat stress response of grazing dairy cows in a temperate climate region

Abstract: The aim of the study was to assess the effect of the summer thermal environment on physiological responses, behaviour, milk production and its composition on grazing dairy cows in a temperate climate region, according to the stage of lactation. Twenty-nine Holstein Friesian multiparous cows were randomly selected and divided into two groups, according to the days in milk, as mid-lactation (99 to 170 d in milk, n = 15) and late lactation (225 to 311 d in milk, n = 14). The comprehensive climate index (CCI) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 50 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Many regions of the world have experienced changes in climate conditions, mainly higher average temperatures, and changes in rainfall patterns, causing very hot summers and prolonged droughts (Meehl et al 2007; Eslamizad et al 2020). Arias et al (2021) reported that grazing dairy systems are highly dependent on environmental factors, making them highly vulnerable to changes in weather conditions. Many researchers have de ned that heat stress is a major challenge for sustainable dairy prod production, compromising not only animal performance but also animal welfare ( 2019) have reported that extremely warm days have at least doubled over the period December-January-February in South America.…”
Section: Introductionmentioning
confidence: 99%
“…Many regions of the world have experienced changes in climate conditions, mainly higher average temperatures, and changes in rainfall patterns, causing very hot summers and prolonged droughts (Meehl et al 2007; Eslamizad et al 2020). Arias et al (2021) reported that grazing dairy systems are highly dependent on environmental factors, making them highly vulnerable to changes in weather conditions. Many researchers have de ned that heat stress is a major challenge for sustainable dairy prod production, compromising not only animal performance but also animal welfare ( 2019) have reported that extremely warm days have at least doubled over the period December-January-February in South America.…”
Section: Introductionmentioning
confidence: 99%